TINGKAT KEPATUHAN PENGGUNAAN OBAT ANTI TUBERKULOSIS (OAT) PADA PASIEN RAWAT JALAN DI PUSKESMAS CILAMAYA KARAWANG - Masita Sari Dewi; Nadia Sagita; Ike Permana Sari (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Background Pulmonary tuberculosis is a direct infectious disease caused by Mycobacterium tuberculosis. The level of patient compliance in taking anti-tuberculosis drugs regularly until they are complete and compliant is one of the factors that determine success in the treatment of pulmonary tuberculosis. The aim was to determine patient characteristics, level of patient adherence and the relationship between the level of adherence to the use of anti-tuberculosis drugs at the Cilamaya Health Center. This research method is a descriptive quantitative approach with a quantitative approach. The tools used for data collection were researchers using a questionnaire at the Cilamaya Health Center for the April-May 2023 period. The results of the study based on gender, the amount of data collection was carried out at the Cilamaya health center, male patients were 54%, age in the age range 15-34 years was 63.5%, high school education was 34.9%, private employee employment was 25.9%, length of treatment of patients 2 months as much as 47.6%, good knowledge as much as 79.4%. In conclusion, the level of patient adherence to the use of anti-tuberculosis drugs (OAT) at the PU Health Center, good adherence rates of 23.8%, moderate 33.3% and poor adherence of 42.9%, patient characteristics include work, knowledge have a significant relationship based on the results of the level of adherence Anti Tuberculosis Drug (OAT) patients because the p value obtained is less than the significant value used, namely 0.005. Value of work (p = 0.001) and knowledge (p = 0.030).